2002
DOI: 10.1243/095765002761034186
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental thermodynamics of fuel cell, engine, and combined heat and power system efficiencies

Abstract: At the 2001 Grove Symposium on Fuel Cells attended by representatives of the world-wide fuel cell industry, fuel cells and fuel cells integrated with gas turbines were discussed. Combined heat and power (CHP) aspects were also discussed. Without exception, ef ciency gures were irrationally based on the measured, Carnot-limited, lower calori c value (CV) of the fuel in energy units J. The rational basis, on the other hand, is the fuel chemical exergy (work units, Ws) calculated via an equilibrium diagram. In Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The construction and designing process of a fuel cell are beginning with the information must be taken into account such as configuration type low voltage/high amperage (LVHA) configuration, or high voltage/low amperage (HVLA) and determination the desired Plate Gap Voltage, Where HHO production depends on the total amount of surface area within the total cell, the more surface area the more HHO can be produced (Barclay, 2002). And the HVLA configuration needs to verify the supply voltage with a good electrical meter.…”
Section: Configurations Of Fuel Cell Constructionmentioning
confidence: 99%
“…The construction and designing process of a fuel cell are beginning with the information must be taken into account such as configuration type low voltage/high amperage (LVHA) configuration, or high voltage/low amperage (HVLA) and determination the desired Plate Gap Voltage, Where HHO production depends on the total amount of surface area within the total cell, the more surface area the more HHO can be produced (Barclay, 2002). And the HVLA configuration needs to verify the supply voltage with a good electrical meter.…”
Section: Configurations Of Fuel Cell Constructionmentioning
confidence: 99%
“…Hence, the management of water in a PEM fuel cell for fulfilling these two conflicting goals, hydrating the membrane and preventing the GDL flooding, is very difficult. [5][6][7][8][9][10] Over the past decades, several methods have been used for water management in different parts of the PEM fuel cell. One of the usual methods for water management in the membrane is humidification of the inlet gases to the fuel cell.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that there is not much difference between the chemical exergy and energy content of fuels. In contradiction, Barclay (2003) showed that chemical exergy for any fuel is roughly 2.5…”
Section: Exergy Analysis In Lcamentioning
confidence: 99%